Does Education Affect HIV Status? Evidence from five African Countries - de Walque, Damien (World Bank, 2012)
Data from the first five Demographic and Health Surveys to include HIV testing for a representative sample of the adult population are used to analyze the socioeconomic correlates of HIV infection and associated sexual behavior. Emerging from a wealth of country relevant results, some important findings can be generalized. First, successive marriages are a significant risk factor. Second, contrary to prima facie evidence, education is not positively associated with HIV status. However, schooling is one of the most consistent predictors of behavior and knowledge: education level predicts protective behaviors such as condom use, use of counseling and testing, discussion of AIDS between spouses, and knowledge about HIV/AIDS, but it also predicts a higher level of infidelity and a lower level of abstinence.